2011
DOI: 10.1016/j.jpainsymman.2010.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioner-Based Models of Specialist Palliative Care at Home: Sustainability and Evaluation of Feasibility

Abstract: This experience suggests that a PHCT-NP-SW model is not sustainable in this urban environment through reimbursement-based revenue, whereas a Hospice-NP model for hospice can be sustainable based on the growth of hospice census. The PHCT-NP-SW model appears to offer benefits, and additional efforts are needed to establish the funding mechanisms to sustain such programs, create mixed models of hospice and nonhospice funding, or provide a basis for sustainability through cost reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Such measures might include standardized team-family meetings to clarify goals of care, development of triggers for palliative care consultation, adherence to established professional EOL care guidelines, proactive consultation of clinical social workers and chaplains, and promotion of generalist palliative care competencies across all disciplines. [58][59][60][61][62] For patients who cannot leave the hospital, teams should be identifying ways to make inhospital care feel more peaceful and dignified (e.g., 24-hour family access, private hospital rooms) and developing policies to ensure high-quality EOL care in the acute care setting (e.g., protocols for ventilator withdrawal and palliative sedation).…”
Section: Discussionmentioning
confidence: 99%
“…Such measures might include standardized team-family meetings to clarify goals of care, development of triggers for palliative care consultation, adherence to established professional EOL care guidelines, proactive consultation of clinical social workers and chaplains, and promotion of generalist palliative care competencies across all disciplines. [58][59][60][61][62] For patients who cannot leave the hospital, teams should be identifying ways to make inhospital care feel more peaceful and dignified (e.g., 24-hour family access, private hospital rooms) and developing policies to ensure high-quality EOL care in the acute care setting (e.g., protocols for ventilator withdrawal and palliative sedation).…”
Section: Discussionmentioning
confidence: 99%
“…Although blinding and loss to follow-up unclearly reported but it is not produce risk of bias because the major measurement is cost effectiveness that assess using computerized system. Two studies conducted retrospective controlled studies (Bookbinder et al, 2011) and (Goodwin et al, 2003) have a good quality of study because follow up measurement completely. This study have grade A recommendation also refer to JBI grading system.…”
Section: Results Of Assessment Methodological Qualitymentioning
confidence: 99%
“…7 One research article demonstrated that an NP model of making home visits in an urban setting for palliative care patients demonstrated a decline in adverse symptoms, better compliance to advance care planning, access to community support, and improvement of managing crisis. 20 The NPs did not generate revenue through billing, as it was less than 50% of their salary costs. They did increase Hospice referrals up to 360% within 7 months, which would have supported their position.…”
Section: Resultsmentioning
confidence: 99%
“…Even so, it closed after 2 years from lack of funding. 20 With patients being discharged earlier out of acute care settings, NP led home care is a viable option, especially to the elderly patients and those with more complex needs. Kumar and McKewan reported 21 that the NPs' ability to reduce costs of hospitalization also leads to an increase in patient benefits and overall reduction in health care costs.…”
Section: Resultsmentioning
confidence: 99%